1965
DOI: 10.1073/pnas.54.1.144
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Streptomycin on antibody synthesis in vitro.

Abstract: Streptomycin inhibits protein synthesis in bacteria by interfering with ribosomal function. SM\1 inhibited the incorporation of amino acids in undefined cell-free systems from Escherichia colil 2 and decreased polyphenylalanine synthesis in E. coli ribosomes when poly U was used as messenger." It was suggested that SMAI acts by interfering with either the attachment or functioning of poly U on the ribosome. SMl did not prevent attachment of poly U to ribosomes, but the presence of poly U on ribosomes made the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1966
1966
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Such roles would be consistent with the findings of amino acid differences between antibodies of different specificities (21) and with data for the colinearity of gene structure and the amino acid sequence of its protein end product (48). Recently, evidence has been adduced for in vitro synthesis of altered antibodies with changed specificity upon addition of streptomycin to lymphoid cultures (22). Presumably, the streptomycin introduced amino acid changes into the antibody molecule by altering the translation process whereby the messenager RNA is decoded at the ribosomal level.…”
Section: Discussionsupporting
confidence: 84%
“…Such roles would be consistent with the findings of amino acid differences between antibodies of different specificities (21) and with data for the colinearity of gene structure and the amino acid sequence of its protein end product (48). Recently, evidence has been adduced for in vitro synthesis of altered antibodies with changed specificity upon addition of streptomycin to lymphoid cultures (22). Presumably, the streptomycin introduced amino acid changes into the antibody molecule by altering the translation process whereby the messenager RNA is decoded at the ribosomal level.…”
Section: Discussionsupporting
confidence: 84%
“…Erythromycin exerts a similar inhibitory effect on chloroplasts in Euglena (46). Streptomycin has been reported to interfere with the production of antibodies in vitro, producing antibodies with altered serological activity (97). However, it is not clear whether this effect is due to a direct action on protein synthesis or to the formation of a streptomycin-antigen complex (98).…”
Section: Effects Of 70s Rubosome Inhibitors In Eucaryotic Cellsmentioning
confidence: 99%
“…Keilova presented in her work influence of streptomycin directly on the explants of heart, aorta and frontal bone of the chick embryo [84]. It was also found by Lawrence that in higher concentration, antibiotics (including penicillin, streptomycin, tetracycline and neomycin) affected not only migration of epithelium around skin explants, but also in some concentrations caused respiratory damage or necrotic changes [83]. In other study, Krueger analyzed effect of streptomycin on protein synthesis in mammalian cells and found that this antibiotic altered the in vitro synthesis of antibody to phage MS-2 in spleen and lymph node cells from immunized rabbits [85].…”
Section: Cell Culture Conditionsmentioning
confidence: 95%
“…Herrell and coworkers found that the different preparation of penicillin exhibited toxic action on mitosis due to some impurities in penicillin preparation. In the comparison with penicillin G, it was practically harmless for cells [82,83]. Keilova presented in her work influence of streptomycin directly on the explants of heart, aorta and frontal bone of the chick embryo [84].…”
Section: Cell Culture Conditionsmentioning
confidence: 99%